DEVELOPING YOUNG EFL LEARNERS' SPEAKING SKILL THROUGH STORYTELLING - Aisyah Risma Triulandari, - (2023)
It is widely acknowledged that storytelling enhances EFL students' speaking ability. However, it seems that there is not much attention to addressing an in-depth picture of how storytelling contributes to Indonesian young EFL learners' speaking skill development, especially in terms of comprehension. This study aimed to explore how storytelling contributes to the development of EFL young learners' speaking comprehension. A case study design was employed in this study, involving a group of three Indonesian EFL young learners aged 12 years old. Storytelling, in this study, was carried out through the implementation of an oral story-sharing cycle consisting of Preparing for Storytelling, Storytelling, Joint Retelling, and Individual Retelling. The data were obtained from video-recording of the real-time observations, a speaking assessment, and students' worksheets. The data were analyzed in thematic analysis by using the data analysis spiral guidelines by Creswell & Poth (2018). The findings indicated that students developed their awareness of the elements of the story through the oral story-sharing stages as well as the scaffolding employed by the teacher. The varied activities done within the story theme in the storytelling stage helped young learners develop their comprehension. Diketahui secara luas bahwa storytelling dapat meningkatkan kemampuan speaking siswa EFL. Namun, tampaknya belum banyak sorotan yang membahas gambaran secara mendalam tentang bagaimana storytelling berkontribusi pada pengembangan keterampilan berbicara pelajar EFL muda Indonesia, terutama pada aspek comprehension atau pemahaman. Penelitian ini bertujuan untuk mengeksplorasi bagaimana storytelling berkontribusi pada pengembangan speaking comprehension pelajar muda EFL. Studi kasus digunakan dalam penelitian ini dengan melibatkan satu kelompok belajar yang terdiri dari tiga pelajar muda EFL Indonesia berusia 12 tahun. Storytelling dalam penelitian ini dilakukan melalui penerapan siklus oral story-sharing yang terdiri dara beberapa stase: Preparing for Storytelling, Storytelling, Joint Retelling, dan Individual Retelling. Data diperoleh dari observasi, penilaian kemampuan speaking, dan lembar kerja siswa. Data dianalisis dalam analisis tematik dengan menggunakan pedoman spiral analisis data oleh Creswell & Poth (2018). Temuan menunjukkan bahwa siswa mengembangkan kesadaran mereka tentang unsur-unsur cerita melalui oral story-sharing serta scaffoldings yang digunakan oleh guru. Berbagai kegiatan yang dilakukan dan masih terkonsep pada tema cerita pada tahap storytelling membantu siswa dalam mengembangkan pemahaman mereka.